2011
DOI: 10.1038/jcbfm.2011.75
|View full text |Cite
|
Sign up to set email alerts
|

Lithium-Mediated Long-Term Neuroprotection in Neonatal Rat Hypoxia–Ischemia is Associated with Antiinflammatory Effects and Enhanced Proliferation and Survival of Neural Stem/Progenitor Cells

Abstract: The aim of this study was to evaluate the long-term effects of lithium treatment on neonatal hypoxicischemic brain injury, inflammation, and neural stem/progenitor cell (NSPC) proliferation and survival. Nine-day-old male rats were subjected to unilateral hypoxia-ischemia (HI) and 2 mmol/kg lithium chloride was injected intraperitoneally immediately after the insult. Additional lithium injections, 1 mmol/kg, were administered at 24-hour intervals for 7 days. Animals were killed 6, 24, 72 hours, or 7 weeks afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
114
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(123 citation statements)
references
References 39 publications
7
114
2
Order By: Relevance
“…treated with normal saline (control group) or lithium chloride (Sigma-Aldrich, Germany; subsequently addressed as lithium only). Lithium dosage was chosen according to previous reports 10,12 with small modifications. Thus, a dose of 1 mmol/kg was i.p.…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…treated with normal saline (control group) or lithium chloride (Sigma-Aldrich, Germany; subsequently addressed as lithium only). Lithium dosage was chosen according to previous reports 10,12 with small modifications. Thus, a dose of 1 mmol/kg was i.p.…”
Section: Experimental Designmentioning
confidence: 99%
“…Whereas one study administered lithium immediately after unilateral global hypoxia-ischemia in neonatal rats, another study evaluated effects of lithium delivery 3 h after transient focal cerebral ischemia in rats. 10,12 Observation periods in these studies were short. In the latter study, effects of lithium were evaluated only over 7 days.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Galectin‐3 has been reported to be produced by activated microglia/macrophages after HI and to be required for resident microglia activation response to HI (Burguillos et al, 2015; Lalancette‐Hébert et al, 2012; Yan et al, 2009). We have previously shown that galectin‐3‐positive microglia is detectable only in areas with overt brain injury (Li et al, 2011). In the present study, we showed that CCL2 expression in the ipsilateral hippocampus of the P9 pups was higher than that of the 3mo mice after HI, indicating that the inflammatory response was more pronounced in the immature brain.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, lithium has been shown to inhibit micro glial activation and cytokine/chemokine secretion in rats. 36,37 In addition, mood stabilizers and antidepressants have an anti-inflammatory effect on isolated monocytes. 38,39 In this cross-sectional study, however, we are not able to make causal inferences with respect to pharmacodynamic effects.…”
Section: Discussionmentioning
confidence: 99%